2020
DOI: 10.1007/s10029-020-02140-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new suture material (Duramesh™) by measuring suture tension in small and large bites techniques for laparotomy closure in a porcine model

Abstract: Purpose After closure of laparotomies, sutures may pull through tissue due to too high intra-abdominal pressure or suture tension, resulting in burst abdomen and incisional hernia. The objective of this study was to measure the suture tension in small and large bites with a new suture material. Methods Closure of the linea alba was performed with small bites (i.e., 5 mm between two consecutive stitches and 5 mm distance from the incision) and large bites (i.e., 10 mm × 10 mm) with Duramesh™ size 0 (2 mm) and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Yurtkap et al (9) reported in their animal study that Duramesh™ had similar results to Polydioxanone (PDS), a traditional laparotomy closure material. They also think that it may help prevent IH by enhancing wound healing thanks to its three-dimensional, macroporous structure (9).…”
Section: Discussionmentioning
confidence: 91%
“…Yurtkap et al (9) reported in their animal study that Duramesh™ had similar results to Polydioxanone (PDS), a traditional laparotomy closure material. They also think that it may help prevent IH by enhancing wound healing thanks to its three-dimensional, macroporous structure (9).…”
Section: Discussionmentioning
confidence: 91%
“…The existing approval is to practice the slight bites method (i.e., 5 mm flesh bites and 5 mm amid two sutures) with sluggishly absorbable stitch ingredients for closing the fascia (4). However, based on the biomechanical issues, the significance of the bite technique remains unidentified (5). A stitch might get through flesh owing to confined force or strain, which might scratch through flesh instantly, ensuing in a ruptured abdomen or an incisional hernia after a while from troubled healing by infection and/or flesh necrosis (6).…”
Section: Introductionmentioning
confidence: 99%